Epstein-Barr Virus LMP2A Interferes with Global Transcription Factor Regulation When Expressed during B-Lymphocyte Development - Portis, Toni (American Society for Microbiology, 2003)
Epstein-Barr virus (EBV) is associated with the development of malignant lymphomas and lymphoproliferative disorders in immunocompromised individuals. The LMP2A protein of EBV is thought to play a central role in this process by allowing the virus to persist in latently infected B lymphocytes. We have demonstrated that LMP2A, when expressed in B cells of transgenic mice, allows normal B-cell developmental checkpoints to be bypassed. To identify cellular genes targeted by LMP2A that are involved in this process, we have utilized DNA microarrays to compare gene transcription in B cells from wild-type versus LMP2A transgenic mice. In B cells from LMP2A transgenic mice, we observed decreased expression of many genes associated with normal B-cell development as well as reduced levels of the transcription factors that regulate their expression. In particular, expression of the transcription factor E2A was down-regulated in bone marrow and splenic B cells. Furthermore, E2A activity was inhibited in these cells as determined by decreased DNA binding and reduced expression of its target genes, including the transcription factors early B-cell factor and Pax-5. Expression of two E2A inhibitors, Id2 and SCL, was up-regulated in splenic B cells expressing LMP2A, suggesting a possible mechanism for E2A inhibition. These results indicate that LMP2A deregulates transcription factor expression and activity in developing B cells, and this likely allows for a bypass of normal signaling events required for proper B-cell development. The ability of LMP2A to interfere with B-cell transcription factor regulation has important implications regarding its role in EBV latency.